Genetic Polymorphism of rs13306146 Affects α2AAR Expression and Associated With Postpartum Depressive Symptoms in Chinese Women Who Received Cesarean Section - Duan, Kai Ming; Fang, Chao; Yang, Si Qi; Yang, Shu Ting; Xiao, Ji Dong; Chang, Huang; Lin, Guo Xin; Zhang, Liang Bin; Peng, Ming Chao; Liu, Zhao Qian; Wang, Sai Ying (Frontiers in Genetics, 2021)
Postpartum depressive symptoms (PDS) is a common psychological and mental disorder after giving birth. Our previous studies showing the application of dexmedetomidine, an α2-AR agonist, can significantly improve maternal sleep, as well as relieve, and reduce the incidence of PDS. This study investigated the association between α2AAR gene polymorphisms and PDS. A total of 568 cesarean section maternal were enrolled. The Edinburgh Postpartum Depression Scale (EPDS) score ≥ 10 was used to diagnose PDS at 42 day after delivery. The SNPs of α2AR were sequenced by pyrophosphate. The effect of rs13306146 A>G polymorphism on α2AR transcription and the regulation of miR-646 on α2AR expression were assessed by dual luciferase reporter assays or gene transfection. Prenatal depression, domestic violence, high stress during pregnancy, and α2AAR rs13306146 AA were all important risk factors for PDS. The transcriptional function of α2AAR rs13306146 AA genotype was decreased compared with GG genotype, and the α2AAR expression level was correspondingly decreased (p <0.05), as the strongest binding ability of miR-646 to α2AAR rs13306146 AA genotype. The effect of α2AAR rs13306146 A>G polymorphism may change the binding ability of miR-646 at the 3’UTR of α2AAR gene, thereby affecting the expression of α2AAR. This study supports the involvement of the NE system in the pathogenesis of PDS. Genotypes of α2AAR may be novel and useful biomarkers for PDS.